Handbook of local government administration - Gargan, John J. (New York: Marcel Dekker, Inc, 1997)
Factors affecting the contexts of local government administration, local govrernment management practices: the importance of doing the basics well, administering generic types of local governments
Keywords: Administración de Rentas